The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12302-016-0093-6
|View full text |Cite
|
Sign up to set email alerts
|

Bile metabolites of polycyclic aromatic hydrocarbons (PAHs) in three species of fish from Morocco

Abstract: BackgroundPolycyclic aromatic hydrocarbons (PAH) are environmental contaminants that pose significant risk to health of fish. Environmental pollution of fish is a topic of rising attention in Morocco. However, only few studies have been carried out so far, describing the potential threat of organic pollution to Moroccan aquatic ecosystem. Two polycyclic aromatic hydrocarbon (PAH) metabolites, 1-hydroxypyrene (1-OH-Pyr) and 1-hydroxyphenanthrene (1-OH-Phen), were identified and quantified from the bile of 18 Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The bile concentration of 3-OH-BaP has been used as an indicator of BaP exposure and biotransformation in many fish species including polar cod (Baake et al, 2016;Baali et al, 2016;Kammann et al, 2017;Song et al, 2019). Indeed, previous studies led on polar cod exposed to either PAHs or crude oil have shown a very high correlation between bile metabolites of PAHs and both cyp1a mRNA expression and EROD activity (Bakke et al, 2016, Bender et al, 2016, Vieweg et al, 2018, Song et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The bile concentration of 3-OH-BaP has been used as an indicator of BaP exposure and biotransformation in many fish species including polar cod (Baake et al, 2016;Baali et al, 2016;Kammann et al, 2017;Song et al, 2019). Indeed, previous studies led on polar cod exposed to either PAHs or crude oil have shown a very high correlation between bile metabolites of PAHs and both cyp1a mRNA expression and EROD activity (Bakke et al, 2016, Bender et al, 2016, Vieweg et al, 2018, Song et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic nature of PAHs plays an important role in their dispersal, deposition and impact within the environment part on the whole ecosystem [10]. Various sources have been reported for their production [11][12][13]. Furthermore, their synthesis can also be made possible by discharge of electricity in decorative items like paints, glue and other protection products [14].…”
Section: Introductionmentioning
confidence: 99%
“…[30,35,39]) as well as mussels and other molluscs [3,6,28,29]. In addition, different Moroccan fish species were analyzed for various contaminants [1,4,8,43]. As a popular food fish in coastal areas of Morocco, European conger from different origins have been previously a target for heavy metal analyses [8,14,42].…”
Section: Introductionmentioning
confidence: 99%